Learning, Social Interaction and Diversity - Exploring Identities in School Practices - Aalsvoort, Geerdina van der; Abreu, Guida de; Hjorne, Eva (SensePublishers : Imprint: SensePublishers, 2012)
The main idea of the book is to contribute to a broader understanding of learning, identity and diversity by presenting actual research findings that were retrieved from classroom settings and related social practices. Learning is to a large extent an ongoing social process as both students and their teachers learn by being part of shared social practices through social interactions that facilitate learning gains. Sociocultural research shows that the organization of schooling promotes or restricts learning, and is a crucial factor to understand how children from a diversity of backgrounds profit from instruction. This is a first urgent issue to be considered by teachers and teacher education in our socio and culturally diverse society. A second issue is the on-going debate about learning as a process that involves the construction of identities in schools and classrooms, and in the transitions between school and home practices. Last but not least, since school practices can be addressed from the perspective of diversity and special educational needs an on-going discussion about optimizing pedagogical approaches is of main importance to allow maximum educational effectiveness. Our potential audience for this book are researchers, post-graduate students in education and psychology, teachers, teacher education, other academics and policy makers.